Social Support for HIV AIDS Sufferers Who Experience Stigma and Discrimination: A Systematic Review - Meo, Christina Marina; Sukartini, Tintin; Misutarno, Misutarno (STRADA : Jurnal Ilmiah Kesehatan, 2021)
HIV AIDS is one of the most stigmatized medical conditions, so people living with HIV / AIDS face various obstacles and need support from their social environment. Stigmatization can hinder seeking medical care, concealing treatment status, and non-compliance. This study aimed to explore the benefits of social support for PLHIV. Application of PRISMA guidelines on four databases (Pubmed, Science Direct, Scopus, Proquest). 17 articles were collected from the 2016 to 2020 study range, in English, and used qualitative, quantitative, and mixed study designs. 1 article using field notes, 6 interviews, and 10 articles using a questionnaire. Stigma reduces the spirit of life which has an impact on the quality of life so that it has a broad impact on physical, psychological, social, and spiritual. Social support has benefits such as managing emotional disorders, adhering to taking ARVs, improving coping and mental health.